Perlunya Syarat Surat Keterangan Catatan Kepolisian Calon Anggota Legislatif Berdasarkan Prinsip Checks And Balances - Nainggolan, Indra Lorenly; Saputra, Rahmat (Universitas Semarang, 2023)
The purpose of this study was to analyze norms that do not regulate the requirements for candidates for legislative members (DPR) without being accompanied by a police record certificate (SKCK) which has a material impact on their duties and responsibilities in establishing law. The research method used in this study is normative juridical with a conceptual approach and a statutory approach. This research is very important in filling public positions because the lack of conditions in question is a form of institutional imbalance in the DPR compared to the requirements for the candidacy of the President and Vice President, Governors, Mayors, and Regents. Even though all of them are public positions that directly receive a mandate from the people. The form of a rule of law requires checks and balances, which upholds Indonesia's constitutional cultural values and places greater emphasis on the harmony and integration of shared values. Meanwhile, the invalidity of the SKCK as a condition for candidacy for members of the DPR is a form of denial. So this has implications for the integrity and quality of prospective members who will occupy the DPR positions. As a law-forming institution, quality and integrity are important parts that must be attached to them, so that in carrying out their duties it will result in the formation of laws that are oriented towards the protection of human rights. The novelty of this research is the analysis of the importance of regulating the requirements for police record certificates in the Election Law as a basis for measuring the filling of public office. Tujuan penelitian ini adalah untuk menganalisis norma yang tidak mengatur syarat calon anggota legislatif (DPR) tanpa disertakan dengan surat keterangan catatan kepolisian (SKCK) yang secara materiil berdampak pada tugas dan tanggungjawabnya dalam pembentukan hukum. Metode penelitian yang digunakan dalam penelitian ini adalah yuridis normatif dengan pendekatan konseptual dan pendekatan perundang-undangan. Penelitian ini sangat penting dalam pengisian jabatan publik, sebab ketiadaan syarat yang dimaksud adalah bentuk ketidakseimbangan kelembagaan DPR dibandingkan dengan syarat pencalonan Presiden dan Wakil Presiden, Gubernur, Walikota, dan Bupati. Padahal semuanya sama-sama jabatan publik yang langsung menerima mandat dari rakyat. Bentuk negara hukum menghendaki adanya checks and balances, yang menjunjung nilai-nilai budaya konstitusional Indonesia dan lebih menekankan harmoni dan integrasi nilai-nilai bersama. Sedangkan ketidakberlakuan SKCK sebagai syarat pencalonan anggota DPR adalah bentuk pengingkaran dimaksud. Sehingga hal ini berimplikasi terhadap integritas maupun kualitas dari calon-calon anggota yang akan menduduki jabatan DPR. Sebagai lembaga pembentuk undang-undang kualitas dan integritas adalah bagian penting yang harus melekat bagi mereka, sehingga dalam menjalankan tugasnya akan menghasilkan pembentukan undang-undang yang beorientasi pada perlindungan hak asasi manusia. Adapun kebaharuan penelitian ini adalah analisis mengenai pentingnya pengaturan mengenai syarat surat keterangan catatan kepolisian dalam UU Pemilu sebagai dasar tolak ukur pengisian jabatan publik.